Importance Et Contributions De La Fete ‘‘Wemԑxwe’’ Dans Le Developpement Des Communes De La Basse Vallee De L’oueme - Basile, Aklamavo; Germain, Gonzallo; Toussaint, Vigninou (European Scientific Journal, ESJ, 2017)
Faced with the inability of the process of decentralization to achieve true grassroots development in Benin, people have turned towards the endogenous development initiatives. These initiatives refer to the community festivals that existed long before the advent of the decentralization process in Benin. This is a typical case of the â€œWÃ©mÔ‘xwÃ©â€ festival in the lower OuÃ©mÃ© valley. This study aims to analyze the importance of socio-cultural realities in the development of localities. In order to understand the importance of community festivals in the development of local authorities, the documentation of this subject is practically non-existent. The participating observation and the field survey made it possible to collect the necessary data from a sample of 200 people. The sample, however, is composed of local elected representatives, local elites, members of the intermunicipal coordination committee of the "WÃ©mÔ‘xwe" festival, development associations, religious leaders, people, and the traditional and notable leaders of the lower valley of the OuÃ©mÃ©. Thus, the technique of â€œsnowballâ€ was used as a sampling method. The SWOT model (Strengths, Weakness, Opportunities, Threats) was used to analyze the results. According to this study, the community festival â€œWÃ©mÔ‘xwÃ©â€ is of great importance in the development of local communities in the lower valley of OuÃ©mÃ©. Due to its yearly celebration, it leaves traces of development on the site having sheltered it. This includes socio-communal infrastructures and paths that were arranged and overlaid. It has invested approximately CFAF 246 324 508 in all the four communes of the lower OuÃ©mÃ© valley from the first edition in 2009 to the sixth edition in 2015.